Produk Domestik Regional Bruto Hijau Sektor Pertanian Subsektor Tanaman Pangan di Kabupaten Hulu Sungai Selatan - Norhidayah; Nur, Muhammad Anshar (PPJP ULM, 2021)
The topic raised in this study was about the green GRDP in the agriculture sector of the food crops subsector in the Hulu Sungai Selatan regency. This research aims to find out the value of green GRDP in the agricultural sector of the food crop subsector in the Hulu Sungai Selatan regency. This research uses the analysis technique of Green GRDP calculation. According to the level of exploration, this type of research data is quantitative research and, according to the level of exploration, is descriptive research. The data used are secondary and are supported by primary data to supplement. The result of this study is the value of green GDRP in the agricultural sector of the reduction of conventional GRDP with depletion and degradation of soil resources. In addition, this study shows the high depletion and degradation value of land resources in the Hulu Sungai Selatan Regency makes the green GRDP value higher than the conventional GRDP value.